Electrical and dielectric behavior of PVA nanocomposites doped with graphene oxide: Effects of doping level and frequency - Boyrazli, M.; Yalcin, Mesut; Dere, Aysegul; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2025)
In this study, the dielectric and electrical properties of polyvinyl alcohol (PVA) nanocomposites with different concentrations of graphene oxide (GO) were systematically investigated. The results showed that GO doping had a significant effect on the dielectric behavior and charge transport properties of the composites. Among the samples, the nanocomposite with low GO content exhibited the highest capacitance, while a general decrease in dielectric constant was observed with increasing GO concentration. The AC conductivity increased with frequency, especially at higher GO contents, indicating improved charge mobility. In addition, the dissipation factor varied as a function of doping, indicating changes in the polarization mechanisms at the interface. These results highlight the role of GO in tuning the dielectric behavior of PVA-based nanocomposites and indicate their potential suitability for use in flexible electronics, sensing platforms and energy storage devices.
Keywords: Graphene oxide (GO); Polyvinyl alcohol (PVA); Dielectric properties; AC conductivity; Flexible electronics